2020
DOI: 10.1155/2020/3057528
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Suture versus Mesh Rectopexy for the Treatment of Persistent Complete Rectal Prolapse in Children: A Comparative Randomized Study

Abstract: Purpose. To compare laparoscopic mesh rectopexy with laparoscopic suture rectopexy. Patients and Methods. The prospective study was conducted at Pediatric Surgery Department, Al-Azhar University Hospitals, Cairo, Egypt between Feb 2010 and Jan 2015. Seventy-eight children with persistent complete rectal prolapse were subjected to laparoscopic rectopexy. Fourteen parents refused to participate. All patients received initial conservative treatment for more than one year. The remaining 64 patients were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…3,4,5 Perineal descent syndrome (PDS) and Rectal prolapse is typically a self-limited problem in children without underlying conditions so its evaluation and treatment are initially conservative . 6,7,8,9 Constipation occurred in our sample in 20 cases (66.6 %); in comparison to 9 of 19 cases (47 %). 7 Fecal incontinence was present in 10 cases (33.3%), a low ratio compared to 5 of 8 cases (62.5%).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…3,4,5 Perineal descent syndrome (PDS) and Rectal prolapse is typically a self-limited problem in children without underlying conditions so its evaluation and treatment are initially conservative . 6,7,8,9 Constipation occurred in our sample in 20 cases (66.6 %); in comparison to 9 of 19 cases (47 %). 7 Fecal incontinence was present in 10 cases (33.3%), a low ratio compared to 5 of 8 cases (62.5%).…”
Section: Discussionmentioning
confidence: 50%
“…The basic objectives of surgical management of perineal descent syndrome and full rectal prolapse thickness is used to restore anatomy and physiology by controlling the external prolapse of the rectum; boost continence, boost bowel function (prevent constipation or evacuation impairment), and minimize the rate of recurrence with lower morbidity and death. 9,11,12 The growing body of literature reinforces the idea that laparoscopic surgical procedures can offer the benefits of low recurrence rates safely, improved clinical outcome, fewer postoperative pain, shorter hospital stay, and early bowel function return in patients with perineal descent syndrome. 2,12 Both laparoscopic rectopexy resection and laparoscopic rectopexy suture were defined with no resection; each having its own merits.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, ABD-ELFATTAH et al, 2022. showed a significant positive result regarding the improvement of continence postoperatively after laparoscopic Resection rectopexy, poste-rior and ventral laparoscopic Mesh rectopexy, meaning that there was a significant improvement of continence after LRR, posterior and ventral LMR (18) . Another study reported that fecal incontinence improved in 92.8% in laparoscopic resection rectopexy without mesh while in mesh rectopexy it was improved in 100% of cases (21) .…”
Section: Discussionmentioning
confidence: 97%
“…Studies by Sahoo et al [38], Usman et al [39], Yehya et al [40], and Bhandarwar et al [41] Operative Time (Minutes)…”
Section: Figure 3: Constipation Improvementmentioning
confidence: 99%